All Days 2010
DOI: 10.2118/131718-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Earth Modeling Improves Drilling Efficiency and Reduces Non-Productive Time (NPT)

Abstract: As time goes by, increase in world energy demand forced oil and gas companies to drill deeper in order to produce more oil and gas for quenching the thirst of human needs. This requires drilling layers with various lithologies with variable characteristics and dealing with more drilling problems as going deeper. Mechanical Earth Model (MEM) should be developed to bypass drilling problems. This model will be used for analyzing instability of the wellbore wall, selecting optimized azimuth and inclination for wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“…The role of geomechanics in minimising excessive drilling costs has been acknowledged by many researchers. Several authors [1][2][3][4][5][6][7] reported the benefit of having a pre-drilling geomechanical model. Their respective drilling challenges have been addressed by means of, but not limited to, the construction of a robust stress profile, the estimation of the rock elastic and strength properties, drilling trajectory evaluation, drilling fluid properties optimization, and casing seat design.…”
Section: Introductionmentioning
confidence: 99%
“…The role of geomechanics in minimising excessive drilling costs has been acknowledged by many researchers. Several authors [1][2][3][4][5][6][7] reported the benefit of having a pre-drilling geomechanical model. Their respective drilling challenges have been addressed by means of, but not limited to, the construction of a robust stress profile, the estimation of the rock elastic and strength properties, drilling trajectory evaluation, drilling fluid properties optimization, and casing seat design.…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, estes tipos de problemas que demandam a inversão de tempos extras não programados são chamados de TNP, o qual é definido como o "tempo no qual a perfuração cessa ou a taxa de penetração é muito baixa" (Moazzeni et al, 2010).…”
Section: Tempo Não-produtivo (Tnp)unclassified
“…Entre as ocorrências que levam à perda de tempo de perfuração, citam-se as seguintes (Moazzeni et al, 2010):  Perda ou dano de equipamentos;…”
Section: Tempo Não-produtivo (Tnp)unclassified
See 2 more Smart Citations